Lifestyle dominates cardiovascular risks in Malaysia (Faculty of Medicine Universitas Indonesia, 2008)
Cardiovascular problem is one of the leading cause of death in Malaysia and now invaded to the sub-urban and rural areas. To prevent and control of this problem, several main risk factors needed to be known and shall be reexamined and ranked according to the priority. The objectives of this research paper was to identify several dominant risk factor related to cardiovascular problem. A cross sectional study was carried out from March 2000 – June 2001 on a total of 8159 rural population aged 18 and above to measure the prevalence of the common cardiovascular risk factors. Those risk factors are systolic blood pressure, diastolic blood pressure, serum cholesterol level, obesity index, blood glucose level, smoking, physical activity and mental stress. Overall prevalence of common cardiovascular risk factors were higher, dominated by physical inactivity (65.7%), hypercholesterolemia – TC:HC (62.3%), mental stress (55.5%) and obesity (53.7%). Smoking was also high at 49.9% especially among men. However systolic hypertension, diastolic hypertension and diabetes mellitus; although increased by age, its prevalence is relatively low at 23.7%, 19.2%, and 6.3% respectively. Cardiovascular risk factors related to lifestyle are much evidenced as compared to risk factors related to the biological influence. Therefore, all initiatives in community health intervention should be mobilized specifically on prevention and control of lifestyle-related risk factors. (Med J Indones 2008; 17: 50-6) Keywords: cardiovascular problem, community intervention, lifestyle-linked risk factors